Natural Zeitgebers Under Temperate Conditions Cannot Compensate for the Loss of a Functional Circadian Clock in Timing of a Vital Behavior in Drosophila. Issue 3 (June 2021) - Ruf, Franziska; Mitesser, Oliver; Mungwa, Simon Tii; Horn, Melanie; Rieger, Dirk; Hovestadt, Thomas; Wegener, Christian
The adaptive significance of adjusting behavioral activities to the right time of the day seems obvious. Laboratory studies implicated an important role of circadian clocks in behavioral timing and rhythmicity. Yet, recent studies on clock-mutant animals questioned this importance under more naturalistic settings, as various clock mutants showed nearly normal diel activity rhythms under seminatural zeitgeber conditions. We here report evidence that proper timing of eclosion, a vital behavior of the fruit fly Drosophila melanogaster, requires a functional molecular clock under quasi-natural conditions. In contrast to wild-type flies, period 01 mutants with a defective molecular clock showed impaired rhythmicity and gating in a temperate environment even in the presence of a full complement of abiotic zeitgebers. Although period 01 mutants still eclosed during a certain time window during the day, this time window was much broader and loosely defined, and rhythmicity was lower or lost as classified by various statistical measures. Moreover, peak eclosion time became more susceptible to variable day-to-day changes of light. In contrast, flies with impaired peptidergic interclock signaling ( Pdf 01 and han 5304 PDF receptor mutants) eclosed mostly rhythmically with normal gate sizes, similar to wild-type controls. Our results suggest that the presence of natural zeitgebers is not sufficient, and a functional molecular clock is required to induce stable temporal eclosion patterns in flies under temperate conditions with considerable day-to-day variation in light intensity and temperature. Temperate zeitgebers are, however, sufficient to functionally rescue a loss of PDF-mediated clock-internal and -output signaling